ASKfm: Motives of Self-Disclosure to Anonymous Questions - Pheseline Felim; Dindin Dimyati; Mohammad Shihab (Jurnal Komunikasi, 2018)
Self-disclosure may happen greatly in social media because nonverbal cues were reduced and their anonymity feature, while they also control their content distribution to certain boundaries based on their own privacy management. The purposes of this research are to know motivation of ASKfm users to disclose their personal information to anonymous questions and how privacy rule criteria such as gender, culture, and context make them want to disclose their personal information to anonymous questions. By using in-depth interview, data were collected from three males and three females aged 18 to 24 years old. They had ASKfm accounts, had answered anonymous questions at least five times, had minimum 100 likes in total, and had revealed personal information to the anonymous questions. ASKfm involved personal evaluation towards rewards and costs received by the users. Participants were motivated to disclose their personal information to anonymous questions to get enjoyment by receiving and answering many anonymous questions as well as relationship building. The motivations indirectly caused self-presentation in which some participants promoted their ASKfm accounts in other social media to get more questions. Collectivistic participants received benefit on enjoyment, while individualistic participants who received benefit on relationship building and maintenance. Participants were more careful in managing disclosures because they were aware of possible risks and possibility of widely personal information distribution to unknown publics by filtering the questions rather than changing the Privacy Settings. KEYWORDS: anonymity, anonymous questions, ASKfm, motivations, privacy management, self-disclosure